2021
DOI: 10.9734/jpri/2021/v33i47b33180
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Quorum Sensing Controlled Virulence Factors and Biofilm Formation by Edible Fruit Extract of Coccinia indica against Pseudomonas aeruginosa

Abstract: Background: Pseudomonas aeruginosa is a Gram-negative opportunistic human pathogen that mainly infects immunocompromised individuals and patients with urinary tract infection and chronic infections of the respiratory pathways, including cystic fibrosis. Many quorum sensing (QS) controlled components such as bio surfactants and swarming motilities play an important role in the establishment of biofilms. Targeting these factors through anti-QS strategies prevent biofilm formation and treating infections. Coccini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Ferula oil and Dorema oil, belonging to the Apiaceae family, and grapefruit ( Citrus paradisi ) essential oils can produce flavonoids, which were found to reduce virulence factor production and interfere with the communication between bacteria [ 157 , 158 ]. Extracts from other natural sources such as the methanol extract of T. bellerica and extracts of Oscillatoria subuliformis , Moringa oleifera , Cuphea carthagenensis , Coccinia indica , and Muntingia calabura L. leaves, have been reported to interfere with the biofilm development and QS of P. aeruginosa [ 159 , 160 , 161 , 162 , 163 , 164 ]. The extracted metabolites of the endolichenic fungi (ELF) Aspergillus quandricinctus of Usnea longissima affect the activities of elastase and protease and prevent the biofilm formation of P. aeruginosa [ 165 ].…”
Section: Inhibition Mechanism Undeterminedmentioning
confidence: 99%
“…Ferula oil and Dorema oil, belonging to the Apiaceae family, and grapefruit ( Citrus paradisi ) essential oils can produce flavonoids, which were found to reduce virulence factor production and interfere with the communication between bacteria [ 157 , 158 ]. Extracts from other natural sources such as the methanol extract of T. bellerica and extracts of Oscillatoria subuliformis , Moringa oleifera , Cuphea carthagenensis , Coccinia indica , and Muntingia calabura L. leaves, have been reported to interfere with the biofilm development and QS of P. aeruginosa [ 159 , 160 , 161 , 162 , 163 , 164 ]. The extracted metabolites of the endolichenic fungi (ELF) Aspergillus quandricinctus of Usnea longissima affect the activities of elastase and protease and prevent the biofilm formation of P. aeruginosa [ 165 ].…”
Section: Inhibition Mechanism Undeterminedmentioning
confidence: 99%
“…In the current investigation, a fast-growing tropical vine Coccinia indica also known as ivy gourd or baby watermelon was selected on the basis of its profound biological and pharmacological activities observed in the literature ( Niazi et al, 2009 , Raje et al, 2013 ). Though there some studies pertaining to its antibacterial ( Devi et al, 2021 ) and antifungal activities however, with different species ( Venkateswaran and Pari, 2003 ) almost all parts of the plants have been used as drug in traditional medical branches of Ayurveda and Unani. Many diseases like leprosy, tumor and jaundice have been treated with extract of fruits and leaves due to its antioxidant nature while, animal studies have shown to reduce plasma glucose levels in diabetes ( Shifali et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%